Peningkatan Kesadaran Kesehatan Mental pada Remaja Melalui Promosi Kesehatan Mental - Ana Fitriani; Syaifullah (CV. Ulil Albab Corp, 2024)
The high number of people suffering from mental health disorders in the current era of globalization means that every individual must increase their understanding and awareness of the importance of mental health. Individuals who have mental health make them able to develop their potential to be able to solve problems faced in their environment. Based on the results of previous research, data was obtained that one in twenty Indonesian teenagers experienced mental disorders in the last 12 months. These figures equate to 15.5 million and 2.45 million teenagers. The large demands faced by teenagers and their inability to adapt to these demands means that teenagers will experience pressure which has an impact on mental health disorders. Based on UU No. 18 of 2014 concerning Mental Health, it is stated that mental health efforts are every activity that aims to create an optimal level of mental health for each individual, family and community through promotive, preventive, curative and rehabilitative services which are carried out in an integrated, sustainable and comprehensive manner by the Government, Regional Government, or Community. So, this can be interpreted as saying that the importance of mental health awareness is very necessary to increase adolescent awareness. The aim of this activity is to broaden insight and increase awareness of mental health for teenagers. The method used is to provide outreach regarding mental health for teenagers. Based on these activities, the results obtained were that 109 of the 120 teenagers who were respondents or around 90.3% understood and were aware of the importance of mental health.